Cryogenic electrolytes - Nazin, S.; Chikina, I.; Shikin, V. (Физика низких температур, 2013)
The emphasis is made on experimentally observed indications of the presence of metastable ion dipoles in
solid helium. Similar quasiparticles possessing positive scattering length for injected electrons are assumed to
exist in liquid phases of cryogenic liquids. The observed phenomena allowing to detect and monitor the behavior
of dipole gas in superfluid helium (referred to as cryogenic electrolyte) are discussed. Most interesting among
these phenomena are: special features of the dielectric behavior of ion dipole gas, details of the temperature dependence
of the ion dipole gas osmotic pressure at the boundary of the liquid ³He–⁴He solution stratification, relaxation
phenomena of collective origin in cryogenic electrolytes, and liquid helium phonon spectrum transformation
due to strong interaction between phonons and heavy dipole quasiparticles.